Literary Echoes from the Margins - Bubíková, Šárka (American & British Studies Annual, 2024)
[review of Milena Kaličanin and Soňa Šnircová, eds. Representations of the Local in the Postmillennial Novel: New Voices from the Margins (Cambridge: Cambridge Scholars Publishing, 2022)]